2008
DOI: 10.1007/s00125-008-0925-z
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in AHI1 are not associated with type 2 diabetes or related phenotypes in Danes: non-replication of a genome-wide association result

Abstract: Aims/hypothesis A genome-wide association study recently identified an association between common variants, rs1535435 and rs9494266, in the AHI1 gene and type 2 diabetes. The aim of the present study was to investigate the putative association between these polymorphisms and type 2 diabetes or type 2 diabetes-related metabolic traits in Danish individuals. Methods The previously associated polymorphisms were genotyped in the population-based Inter99 cohort (n= 6162), the Danish ADDITION study (n=8428), a popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
2
1
Order By: Relevance
“…One of the 18 SNPs we tested in this study, rs1535435, was previously found associated with type 2 diabetes (16), but similarly to a follow-up study investigating the association of this SNP with a range of type 2 diabetes-related metabolic traits (18), we were not able to find this specific SNP significantly associated with fasting blood glucose levels in our population of Mexican Americans. The reasons for lack of replication may be several-fold including variation in patterns of linkage disequilibrium and the genetic basis of their quantitative trait variation, which may be due to ethnicity differences, sample size differences between the cohorts resulting in varying statistical power, and different design strategies.…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…One of the 18 SNPs we tested in this study, rs1535435, was previously found associated with type 2 diabetes (16), but similarly to a follow-up study investigating the association of this SNP with a range of type 2 diabetes-related metabolic traits (18), we were not able to find this specific SNP significantly associated with fasting blood glucose levels in our population of Mexican Americans. The reasons for lack of replication may be several-fold including variation in patterns of linkage disequilibrium and the genetic basis of their quantitative trait variation, which may be due to ethnicity differences, sample size differences between the cohorts resulting in varying statistical power, and different design strategies.…”
Section: Discussioncontrasting
confidence: 47%
“…Two single nucleotide polymorphisms (SNPs) from the AHI1-LOC441171 gene region remained the most significantly associated out of ten SNPs further investigated in a replication study (16). However, a follow-up study was not able to replicate the same SNPs from a study in a Danish population (18) making it unclear as to whether a role for the AHI1 gene in the development of type 2 diabetes and metabolic syndrome exists. Here, we sought to identify novel biological or further genetic evidence for Ahi-1/AHI1 in the metabolic syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…The AHI1-LOC441171 gene region has been linked to T2DM susceptibility among Chinese and Native Americans [ 31 , 32 ]. An initial GWAS done among Finns, Ashkenazi Jews, English, German, and French individuals [ 33 ] has shown that the variants rs1535435 and rs9494266 found in that locus are significantly associated with T2DM (rs1535435, P = 1.86 × 10 −5 ; rs9494266, P = 2.67 × 10 −5 ); yet another GWAS done among the Danish population showed opposite results [ 34 ]. In addition, neither the PDZRN3 gene nor its variant rs11128347 has been linked to poor metformin response; previously, the variant was associated with survival among African-Americans with T2DM on dialysis [ 21 ].…”
Section: Discussionmentioning
confidence: 99%